Analisis Upaya Manajemen Rumah Sakit Dalam Penerapan Budaya Kesehatan dan Keselamatan Kerja (K3) Pasca Akreditasi Pada Sebuah RSUD di Kabupaten Semarang - Naela Fadhila; Sudiro Sudiro; Hanifa Maher Denny (Jurnal Manajemen Kesehatan Indonesia, 2017)
Occupational Health and Safety was very important to protect employees, patient and visitor from occupational illness and occupational accident. Occupational Health and Safety Standard in Hospital was regulated by Decision of The Minister of Health Number 1087/Menkes/SK/VIII/2010. Ahead of accreditation, management has made many efforts to implemented Occupational Health and Safety in Regional Public Hospital of Semarang District. The achievement of accreditation result was 5 star with 80% of its passing grade including Occupational Health and Safety. However, the implementation of Occupational Health and Safety culture post accreditation has not yet been well occupied. The research aimed in analyzing the implementation of Occupational Health and Safety culture at a Regional Public Hospital of Semarang District after accreditation process. It is a qualitative research by using observation and depth interview. The interview was performed on hospital employees, the head of hospital’s accreditation team, Occupational Health and Safety team secretary, medical services management, patients and visitors. The interview based on the research variable such as employee’s assumption, Occupational Health and Safety values, Occupational Health and Safety artifacts and Occupational Health and Safety culture. The result shows that Occupational Health and Safety culture at Regional Public Hospital of Semarang District is not well implemented. Management commitment and good leadership is necessary due to the Occupational Health and Safety culture implementation.